2021
DOI: 10.1186/s12891-021-04182-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL17 antibody Secukinumab therapy is associated with ossification in giant cell tumor of bone: a case report of pathologic similarities and therapeutic potential similar to Denosumab

Abstract: Background Giant cell tumor of bone is a benign, locally aggressive neoplasm. Surgical resection is the preferred treatment method. However, for cases in which resection poses an increased risk to the patient, denosumab (anti-RANKL monoclonal antibody) is considered. Secukinumab is an anti-IL-17 antibody that is used in psoriatic arthritis to reduce bone resorption and articular damage. Case presentation One case of giant cell tumor of bone (GCTB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Given that GCTB is generally diagnosed in women of childbearing age, this important point should be investigated in detail in the future. Recently, Chandler et al [130] reported secukinumab (anti-IL-17 antibody) treatment for psoriatic arthritis with significant intralesional calcifications in a patient with GCTB. Histological examination revealed ossification, new bone formation, and remodeling [130].…”
Section: Denosumab Alone Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Given that GCTB is generally diagnosed in women of childbearing age, this important point should be investigated in detail in the future. Recently, Chandler et al [130] reported secukinumab (anti-IL-17 antibody) treatment for psoriatic arthritis with significant intralesional calcifications in a patient with GCTB. Histological examination revealed ossification, new bone formation, and remodeling [130].…”
Section: Denosumab Alone Therapymentioning
confidence: 99%
“…Recently, Chandler et al [130] reported secukinumab (anti-IL-17 antibody) treatment for psoriatic arthritis with significant intralesional calcifications in a patient with GCTB. Histological examination revealed ossification, new bone formation, and remodeling [130]. A paucity of osteoclast-type giant cells has also been reported [130].…”
Section: Denosumab Alone Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In an experimental model of myocardial brosis in rats, secukinumab administration resulted in a decrease in RANKL levels in cardiac tissues [25]. In a recent case report of giant cell bone tumor, it was reported that secukinumab administration caused a decrease in RANKL levels in bone tissue [41]. In this study, it was observed that secukinumab administration caused an increase in RANKL levels in periodontal tissues, although not statistically signi cant.…”
Section: Discussionmentioning
confidence: 46%
“…Interestingly, real-life data are more encouraging with 82.2% maintained PASI75, 75.3% PASI 90 and 64.4% PASI100 [52]. At the moment the pathogenetic mechanism of secukinumab-related loss of response remains unknown and several hypothesis are present in literature: anti-drug antibodies [53], increased production of TNF-α [46], changes in lifestyle [54][55][56][57], lack of compliance [58] and comorbidities [59]. Thus, different combination therapies may help to counteract the intricate and partially unknown mechanisms of secukinumab secondary failure.…”
Section: Discussionmentioning
confidence: 99%